Genomic Insights Into the Genetic Structure and Natural Selection of Mongolians - Yang, Xiaomin; Sarengaowa,; He, Guanglin; Guo, Jianxin; Zhu, Kongyang; Ma, Hao; Zhao, Jing; Yang, Meiqing; Chen, Jing; Zhang, Xianpeng; Tao, Le; Liu, Yilan; et al. (Frontiers in Genetics, 2021)
Mongolians dwell at the Eastern Eurasian Steppe, where is the agriculture and pasture interlaced area, practice pastoral subsistence strategies for generations, and have their own complex genetic formation history. There is evidence that the eastward expansion of Western Steppe herders transformed the lifestyle of post-Bronze Age Mongolia Plateau populations and brought gene flow into the gene pool of Eastern Eurasians. Here, we reported genome-wide data for 42 individuals from the Inner Mongolia Autonomous Region of North China. We observed that our studied Mongolians were structured into three distinct genetic clusters possessing different genetic affinity with previous studied Inner Mongolians and Mongols and various Eastern and Western Eurasian ancestries: two subgroups harbored dominant Eastern Eurasian ancestry from Neolithic millet farmers of Yellow River Basin; another subgroup derived Eastern Eurasian ancestry primarily from Neolithic hunter-gatherers of North Asia. Besides, three-way/four-way qpAdm admixture models revealed that both north and southern Western Eurasian ancestry related to the Western Steppe herders and Iranian farmers contributed to the genetic materials into modern Mongolians. ALDER-based admixture coefficient and haplotype-based GLOBETROTTER demonstrated that the former western ancestry detected in modern Mongolian could be recently traced back to a historic period in accordance with the historical record about the westward expansion of the Mongol empire. Furthermore, the natural selection analysis of Mongolians showed that the Major Histocompatibility Complex (MHC) region underwent significantly positive selective sweeps. The functional genes, alcohol dehydrogenase (ADH) and lactase persistence (LCT), were not identified, while the higher/lower frequencies of derived mutations were strongly correlated with the genetic affinity to East Asian/Western Eurasian populations. Our attested complex population movement and admixture in the agriculture and pasture interlaced area played an important role in the formation of modern Mongolians.